Impact of Exercise Physiology on Hematological Parameters: Insights into Sports Hematology from a Libyan Cohort - Khairia Laflof (AlQalam Journal of Medical and Applied Sciences, 2025)
Acute exercise induces rapid hematological alterations, including hemoconcentration, leukocyte mobilization, and platelet activation. While such responses are well documented globally, data from North Africa are lacking. To investigate acute changes in complete blood count (CBC) parameters, hemoglobin (Hb), hematocrit (Hct), red blood cell count (RBC), white blood cell count (WBC), and platelet count (Plt) in a Libyan cohort, and to assess the influence of gender and training status. A total of 150 healthy adults (92 males, 58 females; aged 18-35 years) underwent maximal treadmill exercise. Participants were classified as trained (n=80) or untrained (n=70). Venous blood samples were collected 30 minutes pre- and 30 minutes post-exercise. CBC indices were measured using an automated hematology analyzer. Statistical analyses included paired t-tests and two-way ANOVA (gender - training). Hb, Hct, RBC, WBC, and Plt significantly increased post-exercise. Hb rose from 14.0 ± 1.3 to 14.8 ± 1.2 g/dL (p<0.001), Hct from 42.5 ± 3.8% to 44.1 ± 3.7% (p<0.01), RBC from 4.8 ± 0.5 to 5.0 ± 0.5 ×10⁶/µL (p=0.03), WBC from 6.1 ± 1.2 to 6.8 ± 1.3 ×10³/µL (p=0.01), and Plt from 238 ± 46 to 263 ± 49 ×10³/µL (p<0.001). Males exhibited larger platelet increases, while untrained participants showed greater Hb and Hct rises. Acute maximal exercise in Libyan adults induces hemoconcentration, leukocytosis, and thrombocytosis, with gender and training status modulating specific responses. These results provide the first sports hematology dataset from Libya, aligning with international literature and informing athlete monitoring in the region.